Sistem Keamanan Pada Aplikasi Perpustakaan Digital Bank Indonesia iBI library Terhadap Perilaku Cybercrime - Hanifa Salsabila; Anis Masruri; Kartika Puspita Sari; Adzkiyah Mubarokah (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2023)
The purpose of this study was to determine the security system used in the digital library application developed by the Bank Indonesia Library iBI Library against cybercrime behavior such as data thief or data theft, joy computing, hacking or hacking, data diddling and electronic mutilation and data vandalism. The research method uses literature study, which is research to collect data from reading literature from various sources, namely articles, journals and books that are still relevant to the research as a data source to support the research conducted by the author. The results of this study found that the iBI library application security system uses 4 types of security, namely: 1) service information security consisting of confidentiality, integrity and availability, 2) copyright security in accordance with the Law of the Republic of Indonesia Number 28 of 2014 concerning Copyright, 3) collection data security in the form of digital rights management and secure content repository, 4) user security such as single sign on and secure socket layer. In conclusion, the iBI Library application already uses a security system so that libraries and users are safe to use it. This research seeks to analyze the security system that exists in iBI Library, the Bank Indonesia library application to protect the library from potential threats originating from cybercrime. Keywords: Application; Cybercrime; Digital Library; iBI Library; Security System